Behavioral Neurobiology of GABAB Receptor Function - Vlachou, Styliani; Wickman, Kevin (Cham : Springer International Publishing : Imprint: Springer, 2022)
It has been almost forty years since Norman G. Bowery discovered and named this "non-GABAA" receptor the GABAB receptor. It has been almost ten years since the last comprehensive book presentation focused on GABAB receptors. The main goal of this book is to provide the field with a contemporary and comprehensive perspective on the GABAB receptor, its physiological relevance, and its therapeutic potential. The volume is organized into introductory and special interest sections presented by experts who study the GABAB receptor from structural, signaling, pharmacologic, physiological, pathophysiological, and therapeutic perspectives. The book aims to appeal to a broad spectrum of biomedical and clinical scientists - any scholars with an interest in GABAB receptor. The editors hope readers find this work to be thought-provoking, instructive, and informative.
Keywords: Pharmacology; Neurosciences; Psychiatry; Pharmacology; Neuroscience; Psychiatry